(untitled) (The Pakistan Development Review, 2025)
Providing reliable access to electricity to every citizen is a responsibility of the government, which is also considered an imperative condition for improving the life of every household in a country. This study thus aims to find the electricity accessibility as well as affordability condition of the households of Karachi. To collect in-depth electricity information at the household level, this study surveys Karachi city through a questionnaire design. The study surveyed 467 randomly selected households from 18 towns in Karachi. The accessibility and affordability indicators of electricity have been examined using descriptive analysis. Findings from the survey data reveal that although tariff rates are still subsidised for lower consumption households, additional charges such as government charges, TVL fees, fuel adjustment charges, etc., constitute a significant proportion of total electricity bills. The study also recognises households’ cognitive and behavioural aspects of energy use by incorporating these modules in the survey questionnaire. Hence, numerous viable policy options are recommended in the study to successfully implement reforms without compromising the social aspects.